High point narrative structure in mother-child conversations about the past and children’s emergent literacy skills in Costa Rica - Sparks, Alison (2013)
Abstract. The relationship between narrative coherence in mother-child conversations about past events and children’s concurrent emergent literacy was examined in a sample of 32 Spanish-speaking, middle-class, Costa Rican mothers and their preschoolers. Coherence, as expressed in the constituents of high point narrative structure, was measured in reminiscing conversations about everyday events. Our purposes were twofold: 1) to see whether their co constructed narratives in talk about the past could be meaningfully examined for the constituents of high point narrative structure and 2) to explore the links between coherence in these narratives and children’s language and literacy skills. We found a full range of the constituents of high point structure in these conversations, with more advanced forms of narrative structure produced in conversations about the child’s misbehavior. Conversations about misbehavior events were most frequently in the form of classic, high point narratives. In addition, a rich set of relationships between coherence in reminiscing conversations and children’s language and literacy skills were observed. The results revealed similarities in the narrative practices found in this middle-class sample in Costa Rica to both middle-class families in other parts of the world and to conversation and cultural practices unique to Latino communities.